Моделювання показників розміщення продуктивних сил - Степанова, О. В. (ХНУРЭ, 2015)
A questionnaire survey of experts was used in this paper to determine the list of factors and indicators for the assessment of rational distribution of productive forces. Research of the influence on the efficiency of productive forces arrangement was conducted using mathematico-statistic methods of expert assessments. The multi Utility function was applied as an integral index, that is a criterion of optimal distribution of productive forces.
Keywords: розміщення продуктивних сил; моделювання показників